PENGARUH PEMBELAJARAN PROCESS ORIENTED GUIDED INQUIRY LEARNING (POGIL) DAN DISCOVERY LEARNING TERHADAP KEMAMPUAN BERPIKIR ANALISIS SISWA SMAN 27 JAKARTA PADA MATERI SISTEM IMUN - Sartono, Nurmasari; Rusdi, R; Handayani, Rizkia (Universitas Negeri Jakarta, 2017)
Analytical Thining Skills is one of Higher Order Thinking Skills (HOTS). Students are required to have Higher Order Thinking Skills (HOTS) based on Curiculum 2013. Analytical Thining Skills was needed in the process solving a problem in learning process. One of the most difficult matter in grade XI Class is immunity System. With a playing Process Oriented Guided Inquiry Learning (POGIL) dan Discovery Learning hopefully student can improve their analytical thinking skills. This study aimed to determine the influence of POGIL and Discovery Learning toward Student Analytical Thinking Skills On The Matters of Immunity System. This study conducted in 27 Senior High School Jakarta on second semester of academic year 2015/2016 on April until May 2016. The reseach method used was a quasi experiment. The sample was determinate by simple random sampling. Class XI MIA 1 was experiment class Discovery Learning, Class XI MIA 2 was experiment class POGIL, and class XI MIA 3 was control Class. The instrument used was a post-test with objective test formed multiple choice and cause and effect. The normality data test with Kolmogorov-Smirnov and homogeneity test with Uji Bartlett. Base on the statistic test resulted acquired data distribution normal and homogen. Hipotesis test used one way ANAVA test showed the result Ho was rejected on Î±=0,05. This means that there is influence of Process Oriented Guided Inquiry Learning (POGIL) and Discovery Learning toward Student Analytical Thinking Skills On The Matters of Immunity System.